2015
DOI: 10.7196/sajog.983
|View full text |Cite
|
Sign up to set email alerts
|

A clinical audit of female urinary incontinence at a urogynaecology clinic of a tertiary hospital in Durban, South Afric

Abstract: RESEARCHBackground. Urinary incontinence (UI) is a common condition with an increasing prevalence worldwide. Although it is not a lifethreatening condition, it can be very disabling. Objective. To describe the clinical profiles, risk factors, diagnosis, treatment and clinical outcomes of women with different subtypes of UI who attended a tertiary hospital in Durban, South Africa. Methods. A retrospective chart review was performed. A structured data form was used to obtain the relevant information. Results. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The prevalence reported among women with gynaecological issues were similar across studies; 20.2% (95% CI 16-24) [28], 24.0% (95% CI 20-28) [26], 30% (95% CI 27-33) [27] and 39% (95% CI 34-44) [29]. Women with gynaecological issues reported the highest prevalence of UI, while the lowest prevalence was reported among healthy community women.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 80%
See 2 more Smart Citations
“…The prevalence reported among women with gynaecological issues were similar across studies; 20.2% (95% CI 16-24) [28], 24.0% (95% CI 20-28) [26], 30% (95% CI 27-33) [27] and 39% (95% CI 34-44) [29]. Women with gynaecological issues reported the highest prevalence of UI, while the lowest prevalence was reported among healthy community women.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 80%
“…Ten of the 14 studies reported on the risk factors of UI as multiparity, later gestational periods, mode of delivery (including having episiotomy and having an instrumental vaginal delivery (IVD)), pregnancy related constipation, having an underlying respiratory condition during pregnancy, undergoing urethral closure stula repair, having a higher body mass index (BMI) or being overweight, experiencing prolonged labour, engaging in heavy lifting during pregnancy, increasing age of woman, and longer second stage of labour [8, 12,13,[26][27][28][30][31][32][33]. One study reported that women who often experienced constipation were 12 times more likely to have UI, whereas women who sometimes experience constipation were 7 times more likely to have a UI [12].…”
Section: Please Insert Figure 2 Herementioning
confidence: 99%
See 1 more Smart Citation